2021
DOI: 10.3390/cancers13184583
|View full text |Cite
|
Sign up to set email alerts
|

Understanding MNPs Behaviour in Response to AMF in Biological Milieus and the Effects at the Cellular Level: Implications for a Rational Design That Drives Magnetic Hyperthermia Therapy toward Clinical Implementation

Abstract: Hyperthermia has emerged as a promising alternative to conventional cancer therapies and in fact, traditional hyperthermia is now commonly used in combination with chemotherapy or surgery during cancer treatment. Nevertheless, non-specific application of hyperthermia generates various undesirable side-effects, such that nano-magnetic hyperthermia has arisen a possible solution to this problem. This technique to induce hyperthermia is based on the intrinsic capacity of magnetic nanoparticles to accumulate in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 180 publications
(244 reference statements)
1
31
0
Order By: Relevance
“…This approach offers an alternative for certain cancers that may be difficult to surgically remove and for those that reside proximally to vital organs. Since magnetic hyperthermia resolves the issue of nonselective ionizing radiation associated with conventional radiotherapy, treatment options may broaden beyond certain tumours [ 93 ]. Magnetite and maghemite are the most utilized nanoparticle materials for magnetic hyperthermia [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This approach offers an alternative for certain cancers that may be difficult to surgically remove and for those that reside proximally to vital organs. Since magnetic hyperthermia resolves the issue of nonselective ionizing radiation associated with conventional radiotherapy, treatment options may broaden beyond certain tumours [ 93 ]. Magnetite and maghemite are the most utilized nanoparticle materials for magnetic hyperthermia [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Increased temperatures also enhance cell sensitivity to alternative treatments such as chemotherapy and radiation [ 96 ]. Moreover, the increase in cancer cell sensitivity can be attributed to the improved anti-tumour immune response caused by hyperthermia due to its ability to enhance the presentation of tumour antigens, trafficking of leukocytes throughout the endothelium, and NK cell and dendritic cell activation [ 93 ]. The degree of sensitivity is dependent on the time taken between heating and chemotherapy, drug nature and concentration, tumour type, and tumour temperature [ 97 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a different strategy, magnetic NPs can be incorporated into a biocompatible matrix together with drug molecules (bound to the NPs or loaded separately) and magnetic heating can be used to induce the controlled degradation of the matrix and the targeted release of the drug, maximizing its effect and monitoring the treatment [ 6 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Comprehensive review articles can be found in the literature, well illustrating the latest advances and future prospects in biomedical applications of magnetic heating through NPs [ 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%